Early And Late Post-Operative Problems Using The Sublay Vs. Inlay Treatment For Ventral Wall Hernia (Including Incisional): A Comparative Study At A Tertiary Care Centre In Western Maharashtra (Journal of Pharmaceutical Negative Results, 2022)
Introduction: Ventral hernia repair is one of the challenging surgical operations over time. Several surgical techniques for mesh repair have been described (Onlay, Inlay, Sublay, and underlay repairs).Aim and Objectives: This study aim to research and contrast the early and late consequences of ventral wall hernia repair using the Sublay and inlay techniques. Hospital stay, acute postoperative complications, and the recurrence rate were the main areas of investigation.Material and Methods: A prospective study was conducted on 100 patients with ventral hernias who were operated on with sublay mesh repair between June 2020 and July 2022. Patients were admitted through the elective route. The study included fit patients with first-time ventral hernias (primary and incisional). Recurrent hernia, patients with decompensated cardiopulmonary disorders, and bleeding disorders were excluded. The study proforma includes patient’s demographics, operative details, length of stay, postoperative complications.Results: Half of the patients underwent an open sublay (retro muscular) technique and the other half with open inlay (retroperitoneal) method. The ventral hernia was five times more common in females than males. The mean age of presentation was 43.5 years old. The mean operating time was 70 minutes for sublay and 60 minutes for inlay method, and a 3-5 day hospital stay for sublay technique and 5-7 day hospital stay after inlay technique. Paraumblical and incisional hernias represented most cases. Only five cases (5%) developed wound-related complications, while four cases (4%) had a recurrence in inlay technique with no reoccurrence for sublay technique.Conclusion: The sublay mesh repair is a perfect choice for the repair of ventral abdominal hernia. It is associated with a smooth and short hospital stay and the least incidence of complications and recurrence.